Gut anatomy and ultrastructural features of the paunch epithelium in the Neotropical termite Serritermes serrifer (Blattaria, Isoptera, Serritermitidae) - Costa–Leonardo, Ana Maria [UNESP]; da Silva, Iago Bueno [UNESP] (Elsevier, 2022)
Termite gut comprises a long tube divided into several compartments. The well-developed hindgut includes five distinct portions, in which microbial communities are harbored, being responsible for different physiological and digestive processes. An enlarged compartment of the hindgut, the paunch, comprises a sac–like structure whose morphological features differ among termite taxa. The Neotropical termite Serritermes serrifer is the unique inquiline lower termite, and its cryptic habit results in sampling difficulties. Thus, studies regarding this termite species are rare. Here we provide a morphological approach of the gut regions in pseudergates and soldiers of S. serrifer, highlighting the ultrastructure features of the paunch, especially what concerns its function and association with microbial communities. The general morphology of the gut resembles those reported for other “lower termites”, and comprises a short foregut with a small stomodeal valve, a midgut devoid of mixed segment, and a long–compartmentalized hindgut. Eight Malpighian tubules are attached at the mesenteric–proctodeal transition, some of them extending towards the rectum. The ultrastructure of the paunch epithelium reinforces an involvement in content uptake, especially due to the extensive apical invaginations associated with mitochondria. Bacteria are attached to the paunch cuticle by an electron–dense material or are freely distributed in the lumen. The paunch of S. serrifer shares morphological similarities to that of Rhinotermitidae, but cup–like depressions, a likely synapomorphy for the Reticulitermes + Coptotermes + Heterotermes group, were absent. It suggests that bacterial attachment in S. serrifer paunch, as well as the uptake of compounds and microbial metabolites, occur along the epithelium rather than in specific sites, reinforcing the close relationship with basal rhinotermitids, in which such structures are also absent. Moreover, such characters also resemble those reported for Termitidae species.
Keywords: Digestive system; Electron microscopy; Lower termites; Microbiota; Paunch epithelium